MODEL OF UMKM CENTRE MANAGEMENT TO IMPROVE THE EFFECTIVENESS OF BUSINESS ACTORS IN THE COASTAL AREAS IN EAST JAVA - Handini, Sri; Sukesi, Sukesi (Sinergi : Jurnal Ilmiah Ilmu Manajemen, 2019)
The purpose of this study is to depict the effectiveness of UMKM Center Management Model in coastal areas in East Java. It is eventually hoped that the model can be applied by UMKM players and other parties involved in the development of UMKM centers to improve the effectiveness  of  management  application.  This  management  model  is  related  to  human resource management, production management, marketing management, financial management, and business legality. The measurement uses a Likert scale based on the results of the scores to determine whether or not the UMKM center management model is effective. This study is a descriptive one by combining quantitative methods. The sample technique used is purposive sampling. This study uses a survey method that aims to obtain information about the number of respondents who are considered to represent a particular population. Two main types of data collection techniques are employed: questionnaires and interviews.